2020
DOI: 10.1186/s13075-020-02314-9
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and rheumatologists’ perceptions on preventive intervention in rheumatoid arthritis and axial spondyloarthritis

Abstract: Background Individuals at risk of developing rheumatoid arthritis (RA) may benefit from lifestyle or pharmacological interventions aimed at primary prevention. The same may apply to individuals at risk of axial spondyloarthritis (axSpA). Our aim was to investigate and compare the willingness of individuals at risk of RA or axSpA and rheumatologists to initiate preventive intervention. Methods Individuals at risk of RA (arthralgia and anti-citrullinated protein antibodies and/or rheumatoid factor positivity w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
4
14
0
Order By: Relevance
“… 15 This meta-synthesis identified the benefits of predictive testing to motivate lifestyle changes, but also revealed the potential negative emotional impact of testing. In congruence with our synthesis, previous surveys conducted with individuals at-risk of RA 14 42 and spondyloarthropathy 43 highlighted participants’ concerns about preventive medication, particularly with regard to side effects. For example, in one such study, willingness to take preventive medication decreased by approximately half with the possibility of mild side effects.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“… 15 This meta-synthesis identified the benefits of predictive testing to motivate lifestyle changes, but also revealed the potential negative emotional impact of testing. In congruence with our synthesis, previous surveys conducted with individuals at-risk of RA 14 42 and spondyloarthropathy 43 highlighted participants’ concerns about preventive medication, particularly with regard to side effects. For example, in one such study, willingness to take preventive medication decreased by approximately half with the possibility of mild side effects.…”
Section: Discussionsupporting
confidence: 80%
“…For example, in one such study, willingness to take preventive medication decreased by approximately half with the possibility of mild side effects. 43 Synonymous with our review findings, previous studies have also revealed that the decision to engage with preventive interventions depends on the effectiveness of these treatments, 14 42 the opinions of trusted healthcare professionals, 42 individuals’ perceptions of how severe the disease is 43 and when their risk of developing the disease is increased. 14 43 However, in contrast to our findings, one previous study found that mode of drug administration did not influence at-risk individuals’ decisions to take preventive treatment.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations